The Consequences of the "Perestroika" Policy in Social Life in the Uzbek SSR - Dilmurodov Farrukh Rustam oglu (Scientific Trends, 2025)
This article analyzes the socio-economic changes carried out in the Uzbek SSR during the period of Perestroika and the problems that arose in this process. The relevance of the article is that it studies the impact of the Perestroika period, which was an important stage in the history of Uzbekistan, on local socio-economic life. Today, the lessons of this period play an important role in correctly assessing the post-independence development strategies of Uzbekistan. The main goal of the research is to reveal the essence of the reforms carried out in the Uzbek SSR during the years of Perestroika, to show their impact on society and the economy, and to analyze the mistakes and shortcomings made. In conducting our research, historical-analytical, statistical and comparative methods were used, and an analytical approach was implemented based on archival documents, official data and the press of the time. The policy of perestroika, along with positive results, also caused a number of serious shortcomings. In particular, the over-regulation of cotton production, the inefficiency of the socialist economy, problems in national relations, and the agricultural crisis have increased public distrust of reforms. Learning from these mistakes is important for Uzbekistan's current and future reform policies.
Keywords: Perestroika, Gorbachev, the Aral Sea problem, Cotton, economy, national relations, agriculture.